2019
DOI: 10.3389/fmicb.2019.00545
|View full text |Cite|
|
Sign up to set email alerts
|

The Capsule Depolymerase Dpo48 Rescues Galleria mellonella and Mice From Acinetobacter baumannii Systemic Infections

Abstract: The emergence of multidrug- and extensively drug-resistant Acinetobacter baumannii has made it difficult to treat and control infections caused by this bacterium. Thus, alternatives to conventional antibiotics for management of severe A. baumannii infections is urgently needed. In our previous study, we found that a capsule depolymerase Dpo48 could strip bacterial capsules, and the non-capsuled A. baumannii were significantly decreased in the presence of serum complement in vitro. Here, we further explored its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Other studies have also demonstrated that a single administration of capsular depolymerases could significantly protect mice infected with E. coli (K1, K2, K5, and K30) (13,14) and K. pneumoniae (K1, K5, K64, and KN2) (15)(16)(17)(18). A recent study also showed that a capsule depolymerase administered intraperitoneally could rescue 100% of mice with A. baumannii systemic infections (19). In that study, the A. baumannii strain used has an undefined capsule type, which enabled us to correlate the activity with our K2 depolymerase.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have also demonstrated that a single administration of capsular depolymerases could significantly protect mice infected with E. coli (K1, K2, K5, and K30) (13,14) and K. pneumoniae (K1, K5, K64, and KN2) (15)(16)(17)(18). A recent study also showed that a capsule depolymerase administered intraperitoneally could rescue 100% of mice with A. baumannii systemic infections (19). In that study, the A. baumannii strain used has an undefined capsule type, which enabled us to correlate the activity with our K2 depolymerase.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, since capsule removal by the K2 depolymerase attenuated the pathogenicity of the cells and prolonged the larval life span, it was demonstrated that the capsule K2 type is a major virulence factor of A. baumannii. Generally, other researchers have also shown success in preventing and treating the lethal effects of encapsulated K. pneumoniae (K3, K21, and K36) (31,35) and A. baumannii (undefined capsule type) (19) with single injections of capsular-specific depolymerases. However, these models have administered enzymes immediately after infection (5 min or less), which may raise the question of whether they are only providing a protective effect rather than a therapeutic one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the phylogenetic diversity (almost 50% non-GC2 isolates) and the even spread across the three hospitals, we show that there is a high degree of strainto-strain capsule variability, and development of depolymerase therapeutics will need to account for the challenge of a wide range of capsule types. Nevertheless, a recent study has demonstrated the potential of capsule depolymerase against A. baumannii in a Galleria mellonella (wax moth) larvae infection model and protection of both normal and immunocompromised mice from lethal peritoneal sepsis (Liu et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of the bacterial capsule reduces biofilm formation and, as a result, antibiotic resistance: so, using bacteriophage depolymerases to eliminate the biofilm in the treatment of bacterial infections was proposed [ 53 , 54 , 55 ]. Various isolated phages against A. baumannii were shown to encode depolymerase, which successfully eliminates the capsular exopolysaccharide of the bacterium [ 53 , 56 , 57 ]. Thus, endolysin (LysAB3) of phage φAB3 specific to A. baumannii effectively eliminates the biofilm associated with A. baumannii in vitro [ 58 ].…”
Section: Methodsmentioning
confidence: 99%